2007
DOI: 10.1590/s1413-78522007000200003
|View full text |Cite
|
Sign up to set email alerts
|

Influência do diâmetro do orifício piloto na resistência ao arrancamento dos parafusos do corpo vertebral

Abstract: Foram realizados ensaios mecânicos com o objetivo de avaliar a influência do diâmetro do orifício piloto em relação ao diâmetro interno do parafuso na resistência ao arrancamento dos parafusos do sistema de fixação vertebral aplicados no corpo da vértebra. O estudo foi realizado em duas etapas. Na primeira etapa foram utilizados corpos de prova de poliuretana para a colocação de parafusos de 5mm e, 6mm , e na segunda etapa os parafusos foram inseridos na face lateral dos corpos das vértebras lombares de suínos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
(16 reference statements)
0
3
0
9
Order By: Relevance
“…Screw insertion into the model was limited to 30 mm, and this was performed in order to avoid screw head influence, making the models further standardized for photoelastic analysis. This limitation on screw's insertion into the model was also intended to simulate the models used by Defino et al 19 as well, in which mechanical pullout assays of screws fixated on the lateral surface of lumbar vertebral bodies of pigs. For these models, the authors limited screw insertion to 30 mm in order to prevent opposite vertebral body cortical from being exceeded.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Screw insertion into the model was limited to 30 mm, and this was performed in order to avoid screw head influence, making the models further standardized for photoelastic analysis. This limitation on screw's insertion into the model was also intended to simulate the models used by Defino et al 19 as well, in which mechanical pullout assays of screws fixated on the lateral surface of lumbar vertebral bodies of pigs. For these models, the authors limited screw insertion to 30 mm in order to prevent opposite vertebral body cortical from being exceeded.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…It has been reported that the holding power of the pedicle screw is significantly influenced by the size and technique of the pilot hole [5,7,14,15,33]. For selftapping cylindrical pedicle screws, reduction of the pilot hole diameter in relation to the screw outer diameter increases screw pullout force; however, the correlation of the pilot hole with screw internal (core) diameter was not mentioned [4,6,12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…O diâmetro e o modo de preparo do orifício-piloto são variáveis que podem influenciar a ancoragem dos parafusos do sistema de fixação vertebral, alterando sua resistência ao arrancamento (2,4,(10)(11)(12) . Este estudo foi elaborado a partir da hipótese de que as alterações das propriedades mecânicas dos implantes, relacionadas com a confecção do orifício-piloto, estariam vinculadas às alterações microscópicas estruturais do tecido ósseo presente ao redor do implante.…”
Section: Discussionunclassified
“…Essa ancoragem também é influenciada pela densidade mineral óssea, torque de inserção, diâmetro externo do implante e preparo do orifício-piloto (1)(2)(3) . No osso esponjoso, a utilização de orifício-piloto de menor diâmetro que o diâmetro interno do parafuso (alma do parafuso) provoca a compactação do osso das paredes do orifício-piloto.…”
Section: Introductionunclassified